Rehabilitation of Housing for Disaster Affected People: A Case Study of Landslide at Chittagong, Bangladesh (Journal of Bangladesh Institute of Planners, 2018)
Housing provides shelter and living environment to human beings. Population growth rate, urban migration and natural disasters are making it more complicated and strenuous and also reducing the housing stock of a country. Landslide is one of the natural disasters which directly and indirectly impacts on housing every year. Chittagong the second largest city and industrial and commercial hub with the largest seaport of Bangladesh has undergone steady and rapid unplanned urbanization since independence. Chittagong urban area is facing landslide disaster in rainy season. On the other hand, the City is facing housing shortage and the shortage in the number of housing units is increasing. In this paper, it is an attempt to find out the way with a proposal of selecting a site for rehabilitation of housing scheme which is economically viable for that affected people in Chittagong City.JBIP, Vol. 11, 2018 (Printed in June 2020), pp. 137-156